The Sa'dan-Toraja A Study of Their Social Life and Religion. I: Organization, Symbol and Beliefs - Nooy-Palm, Hetty (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1979)
The present volume consists of two parts, Part I dealing with the natural surroundings and the social and territorial organization of the Sa'dan-Toraja, Part 11 with religious notions, natural and material symbols, and priestly organization. Volume 11, which will hopefully appear in due time, will contain a description of Sa'dan-Toraja rituals, those associated with the East in Part 111, and those with the West in Part IV.